(3eNJUQ aj GdCOhjI GdeQcHIs - (3eMeO Hf HgQGe Hf eMeO GdbdGfSj GdSeQbfOj, HOQGdOjf , J (B590 (3g` s
(3ChdgG (B:s
(3bGd GdEeGe GdHGQY HOQ GdCFeI eMeO Hf HgQGe Hf eMeO GdbGdfSi GdWHjH GdMeO ddg GdMcje GdbGgQ CeG HYO abO OYGfi Edi Cf CLeg gPG GdeNJUQ Cfi QCjJ Ld GdbQGHGPjfGJ eTMhfI ef fSN GdCOhjI GdeQcHI s
(3BNQgG (B:s
(3eQGQI GdKhQ EPG NdW HgG TMe GdMfXd hGQGRjGfL eObhbjf hdWN efgG UQI ef Hg bhdfL hEMJHGS GdWHY CSgdg , GdMjGJ GdeJhdOi ai GdHWf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B122s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdWHs